2011
DOI: 10.3892/ijmm.2011.763
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of atopic dermatitis-related symptoms by Perilla frutescens Britton

Abstract: Abstract.To ascertain whether an aqueous fraction of Perilla frutescens Britton (PfB/af) has advantageous anti-atopic dermatitis activity, we used a 2,4-dinitrofluorobenzene (DNFB)-induced animal model of atopic dermatitis symptoms to investigate the effects of the extract. We performed an ear swelling assay by comparing thickness of the DNFB-induced ear, and measured the numbers of eosinophils as well as total immune cells. We analyzed the expression levels of matrix metalloproteinase (MMP)-9, interleukin (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Perilla has been demonstrated to exert antiobesity, anti-dyslipidemia, antioxidant, and anti-infammation [ 13 19 ]. Recently, some researches focused on its antiallergic effects [ 20 23 ]. The studies suggested water extract of Pf inhibited histamine release from mast cells [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perilla has been demonstrated to exert antiobesity, anti-dyslipidemia, antioxidant, and anti-infammation [ 13 19 ]. Recently, some researches focused on its antiallergic effects [ 20 23 ]. The studies suggested water extract of Pf inhibited histamine release from mast cells [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that MMP-2 was expressed in the epidermis and dermis from patients with atopic dermatitis, while MMP-9 was not upregulated (33). However, another study demonstrated that MMP-9 was upregulated in a mouse model of DNFB-induced atopic dermatitis, and the IL-31 and T-bet gene were also expressed in the ear epidermis (34). MMP-2 and -12 have been shown to be upregulated in the lung by inspiratory resistive breathing (35).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that different extractions of Perilla frutescens exert various beneficial effects on airway inflammatory and hypersensitive disorders [19], [20]. Oh et al have reported an ethanol extract of Perilla frutescens leaf and rosmarinic acid, the major component of the extract, is able to reduce expression of IL-1β, IL-6 and TNF-α in the nasal mucosa tissue of ovalbumin-sensitized mice [19].…”
Section: Discussionmentioning
confidence: 99%